ANALYSIS OF BASIC FACTORS AFFECTING STOCK RETURNS OF PROPERTY AND REAL ESTATE COMPANIES IN THE INDONESIAN STOCK MARKET - Fernando, Muhammad Faiz; Iqbal, Muhammad; Hilmy, Muhammad; Baihaqi, Muhammad; Asteria, Beta (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to determine the effect of fundamental factors, namely the Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) on stock returns on the Indonesia Stock Exchange for the 2016-2020 period. The research design is a causality study. The population of this study uses property and real estate companies that have been and are still listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique was purposive sampling and a sample of 15 companies was obtained. Methods of data collection using documentation techniques. Research data were analyzed using multiple linear regression. Based on the results of data analysis using the partial test (t- test) the Debt to Equity Ratio variable has no effect on stock returns with a significance value of the DER variable that is equal to 0.484 which is greater than 0.05. DER has a negative relationship with returns. The higher the DER ratio, the lower the return generated by the company. Total Asset Turn Over has a positive effect on stock returns with a significance value of the TATO variable which is 0.014 which is smaller than 0.05. The ability of the independent variables in this study to affect the dependent variable by 6.4%, while the remaining 93.6% is explained by variables other than the independent variables in the study.